PENGARUH PEMBELAJARAN PROJECT BASED LEARNING (PjBL) DENGAN MEMANFAATKAN GOOGLE EARTH TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN GEOGRAFI - Septina Nurazizah; Dedi Hermon (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the implementation of the Project Based Learning (PjBL) model with the help of Google Earth media on students' learning interest in geography learning at SMAN 1, Payakumbuh District. The research method used is a quasi-experimental method with a nonequivalent control group design. The research sample consisted of class X.E2 as the experimental class and class X.E3 as the control class which were selected randomly. Data on students' learning interest were obtained through a questionnaire, while data on learning outcomes were obtained through a test, then analyzed using prerequisite tests and hypothesis tests with paired sample t-tests. The results showed that the implementation of the PjBL model assisted by Google Earth had a positive effect on students' learning interest, as indicated by the average posttest of the experimental class of 86.00 and the control class of 71.43.